Barriers to genome editing with CRISPR in bacteria - Vento, Justin M. (J Ind Microbiol Biotechnol, 2019)
Genome editing is essential for probing genotype-phenotype relationships and for enhancing chemical production and phenotypic robustness in industrial bacteria. Currently, the most popular tools for genome editing couple recombineering with DNA cleavage by the CRISPR nuclease Cas9 from Streptococcus pyogenes. Although successful in some model strains, CRISPR-based genome editing has been slow to extend to the multitude of industrially-relevant bacteria. In this review, we analyze existing barriers to implementing CRISPR-based editing across diverse bacterial species. We first compare the efficacy of current CRISPR-based editing strategies. Next, we discuss alternatives when the S. pyogenes Cas9 does not yield colonies. Finally, we describe different ways bacteria can evade editing and how elucidating these failure modes can improve CRISPR-based genome editing across strains. Together, this review highlights existing obstacles to CRISPR-based editing in bacteria and offers guidelines to help achieve and enhance editing in a wider range of bacterial species, including non-model strains.